New Results in the Startpoint Theory for Quasipseudometric Spaces. (17th November 2014) - Gaba, Yaé Ulrich
Abstract : We give two generalizations of Theorem 35 proved by Gaba (2014). More precisely, we change the structure of the contractive condition; namely, we introduce a functionΦ instead of a simple constantc .